Interactions among the early Escherichia coli divisome proteins revealed by bimolecular fluorescence complementation. (19th August 2013) - Pazos, Manuel; Natale, Paolo; Margolin, William; Vicente, Miguel; Vicente, Miguel; Ayala, Juan; Daley, Daniel
Summary We used bimolecular fluorescence complementation (BiFC) assays to detect protein‐protein interactions of all possible pairs of the essential Escherichia coli proto‐ring components, FtsZ, FtsA and ZipA, as well as the non‐essential FtsZ‐associated proteins ZapA and ZapB. We found an unexpected interaction between ZipA and ZapB at potential cell division sites, and when co‐overproduced, they induced long narrow constrictions at division sites that were dependent on FtsZ. These assays also uncovered an interaction between ZipA and ZapA that was mediated by FtsZ. BiFC with ZapA and ZapB showed that in addition to their expected interaction at midcell, they also interact at the cell poles. BiFC detected interaction between FtsZ and ZapB at midcell and close to the poles. Results from the remaining pairwise combinations confirmed known interactions between FtsZ and ZipA, and ZapB with itself.